Analysis of the influence of the tubes constrained structure of contra-flow vertical shell and tube heat exchanger on heat transfer ability with natural circulation. Issue 1 (July 2021) - Peng, Kangwei; Wang, Xiaoding; Song, Guangdong; Liu, Mengmeng
Abstract: In order to verify the effect of the combined restraint form of straight strip and corrugated strip on the heat transfer capacity of shell-tube heat exchanger with natural circulation. The physical model and mathematical model of the local heat exchange section of the heat exchanger are established by using ICEM and Fluent to carry out numerical simulation. The calculation results of three-dimensional flow field and temperature field of the heat exchange section are solved and analysed to obtain the resistance characteristics of the tube bundle of shell-and-tube heat exchanger under the restriction of corrugated strip and straight strip with natural circulation and the influence at the temperature field.